Modern Digital-Analog Jamming Transmitter - Amer F. Sheet (NTU Journal of Engineering and Technology)
Abstract- Principle analysis results provide construction new digital-analog jammers from the point of view minimizing out-of-band undesirable electromagnetic radiation. Reviewed methods of compensating for nonlinear distortions, which are suitable for use in power amplifiers of jammers, based on linearization methods of the characteristics of powerful amplifying devices. The substantiation of a new compensation method for eliminating undesirable combination components in the spectrum of jamming transmitters with quadrature modulation (the method of depletion of the input signal spectrum).